Roles of Histone H3-Lysine 4 Methyltransferase Complexes in NR-Mediated Gene Transcription - Lee, Seunghee (Prog Mol Biol Transl Sci, 2009)
Transcriptional regulation by nuclear hormone receptors (NRs) requires multiple coregulators that modulate chromatin structures by catalyzing a diverse array of posttranslational modifications of histones. Different combinations of these modifications yield dynamic functional outcomes, constituting an epigenetic histone code. This code is inscribed by histone-modifying enzymes and decoded by effector proteins that recognize specific covalent marks. One important modification associated with active chromatin structures is methylation of histone H3-lysine 4 (H3K4). Crucial roles for this modification in NR transactivation have been recently highlighted through our purification and subsequent characterization of a steady-state complex associated with ASC-2, a coactivator of NRs and other transcription factors. This complex, designated ASCOM for ASC-2 complex, contains H3K4-methyltransferase MLL3/HALR or its paralogue MLL4/ALR and represents the first Set1-like H3K4-methyltransferase complex to be reported in vertebrates. This review focuses on recent progress in our understanding of how ASCOM-MLL3 and ASCOM-MLL4 influence NR-mediated gene transcription and of their physiological function.